Acid citrate dextrose formula A versus unfractionated heparin for anticoagulation of salvaged red blood cells in cardiac surgery. Issue 12 (15th November 2022) - Erdoes, Gabor; von Stegmann und Stein, Christiane; Eberle, Balthasar; Gerber, Daniel
Abstract: Red blood cell salvage plays an important role in reducing the use of allogeneic blood transfusion during cardiac surgery. While there is consensus as to the benefit of employing cell salvage systems, there are no clear recommendations on the anticoagulant used for salvaged blood. In eight patients undergoing elective cardiac surgery at our university hospital's cardiovascular center, the authors describe hemodynamic effects of salvaged autologous blood transfusion when either unfractionated heparin or acid citrate dextrose formula A was used as the anticoagulant. Mean arterial pressure, heart rate, central venous pressure and acid–base status of the autologous red blood cell concentrate were compared between patients receiving autologous blood anticoagulated with acid citrate dextrose formula A versus unfractionated heparin. A clinically relevant decrease in mean arterial pressure (median change, − 19 mmHg [min −29; max −1] and marked acidosis [group median <6.30 [<6.30; 6.49] was observed in group acid citrate dextrose formula A. Acid citrate dextrose formula A anticoagulant for autologous red blood cell salvage has the potential to cause major adverse hemodynamic events during free‐flowing re‐transfusion of autologous red blood cell concentrate. Acute ionized hypocalcemia and acidemia may ensue from residual citrate in the supernatant of red blood cell concentrate reconstituted in unbuffered saline.